Universal Design and Accessibility Performance in Public Buildings: Perspectives of Malaysia’s Public Works Department - Adam, Noor Ruzaini; Aziz, Azlina; Sulaiman, Shuhaila (MAJ - Malaysia Architectural Journal, 2025)
Universal design and accessibility in Malaysia have gone through various improvement and showing a steady progress aligning with Goal 9, 10 and 11 of United Nation’s 2030 Agenda for Sustainable Development. However, the accessibility performance of public buildings remained unknown despite the claim. Public Works Department (JKR) as the national technical agency in executing the country’s physical development shall ensure public buildings and infrastructure employs sustainable strategy, in particular application of accessibility and universal design. Therefore, the purpose of this article is to evaluate accessibility performance of public buildings in Malaysia. The methodology used is a case study of twelve (12) public buildings of various types located in Peninsular Malaysia. The selected buildings were assessed using the checklist derived from Malaysia Standard MS1184:2014 Universal Design and Accessibility in the Built Environment Code of Practice (Second Revision). The study showed that newly built health facility building obtained the highest score whereas school buildings scored the lowest. The findings from the assessments were further analyzed according to the checklist criteria to propose recommendation on how to provide fully accessible public buildings. In conclusion, although universal design and accessibility have been gazetted as statutory requirements since 2008, public buildings still have a long way to go in ensuring the facilities are inclusive and fully accessible to all. Therefore, synchronization of budget prioritization and stakeholders’ awareness will help in accomplishing seamless access and function of public buildings.